Pengaruh Current Ratio, Debt to Equity Ratio, Return on Equity Terhadap Earning Per Share pada Perusahaan Sub Sektor Batu Bara yang Terdaftar di Bursa Efek Indonesia 2014-2018 - Ach. Faruq; I Made Wianto Putra; Ni Putu Riasning (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Warmadewa, 2021)
This study aims to analyze the effect of Current ratio, Debt to equity Ratio, Return on Equity on Earning per Share in Coal Sub-Sector Companies Listed on the Indonesia Stock Exchange 2014-2018. The research data was collected through data analysis on the company's financial position report and income statement. The type of data used is qualitative data. The population in this study were 21 companies which were determined by purposive sampling method. The data analysis technique used descriptive statistical analysis, normality test, multicolonaryity, heterocedacity, autocoleration test, multiple linear regression analysis, and hypothesis testing. The results of the analysis conclude that the current ratio has a positive effect on earnings per share. Debt to equity has a negative effect on earnings per share. Return on equity has a positive effect on earnings per share of coal sub-sector companies on the Indonesia Stock Exchange (BEI) 2014-2018.